Where did you hear that? Narrative Competition and Societal Instability in Burkina Faso - Wolfel, Richard L.; Fairfield, Christiana; Richmond, Amy; Grannis, Rick; Womack, Scott; Moriarty, Daniel; Grazaitis, Pete; Wu, Elizabeth (Scientia Militaria - South African Journal of Military Studies, 2024)
Coups do not occur randomly. They are the result of significant shocks, or triggers, to a societal system, which is especially catastrophic in societies with high levels of vulnerability. It is often in this context of high vulnerability that global powers act to gain influence throughout the world. Narrative competitions, or information campaigns, are becoming increasingly important as an approach to projecting influence at international scale. Socio-cultural and economic triggers of societal instability are critical spaces where narrative and indirect competitions occur. Explaining how competitors manipulate these country-specific triggers as part of an influence campaign is essential to understanding modern geopolitics. The study on which this article reports, used the Modeling Dense Urban Networks analytical model to explain the influence of economic, geographical, and political changes on the opinion of the local population on crucial societal tipping points in Burkina Faso. Burkina Faso is a region with intense societal vulnerability due to economic inequalities, regional instability brought on by the ongoing conflict in the Sahel, significant environmental security issues, and a distrust of the government and the former colonial power, France. These internal factors of instability strongly influenced the two military coups in 2022. In addition to the internal factors of instability, Burkina Faso is an area of powerful competition between several global powers, each providing a narrative to manipulate societal opinion around these local issues of vulnerability to promote their influence in Burkina Faso at the expense of their adversaries.